Hunter, knight, ruler: Markers of social roles in the Russian translation of Wolfram von Eschenbach’s ‘Parzival’ - A. V. Khokhlova (Шаги, 2024)
The article analyzes the depiction of social roles in the Russian translation of Wolfram von Eschenbach’s ‘Parzival’. During his travels, the protagonist has to change three social roles: Parzival begins his journey as a hunter, then there is his transformation into an ideal knight, and finally he becomes the ruler of the Grail Castle. In the original text, each of these roles is accompanied by certain markers that were clear to the medieval listener but are not always obvious to the modern reader. L.V. Ginzburg’s translation allows inaccuracies, makes many digressions from the original text and paraphrases certain episodes. Naturally, this also affects the descriptions of Parzival’s social roles. Ignoring and neglecting seemingly insignificant markers leads to an inaccurate understanding of the medieval romance. However, to convey all the nuances that are inaccessible to the modern reader would require not so much a more precise poetic idiom, as an extensive historical and cultural commentary, missing from modern Russian-language editions of ‘Parzival’, that would help create the necessary context around the work. The ruler in the medieval novel is the ideal knight, and a knight is always a hunter; Parzival’s transition from one state to another, from one social role to another, is smoothed out in the Russian translation, and the markers that allowed Wolfram von Eschenbach to label each of the social roles more precisely and sharply are lost.